BREAST-CONSERVING SURGERY AFTER NEOADJUVANT CHEMOTHERAPY IN BREAST CANCER PATIENTS - A. R. Bosieva; M. V. Ermoshchenkova; N. N. Volchenko; A. D. Zikiryahodjaev (Сибирский онкологический журнал, 2021)
The purpose of the study was to present the most recent data on the outcomes of breast-conserving surgery after neoadjuvant chemotherapy for breast cancer patients.Material and methods. We analyzed relevant publications available in the pubmed, cochrane library, e-library databases between 1990 and 2020, and 24 of them were used to write this review.Results. Neoadjuvant chemotherapy for breast cancer patients is currently a widespread treatment option. The main advantage of this type of treatment for patients with early stage breast cancer is the feasibility of performing breast-conserving surgery in cases of partial or complete clinical response and, therefore, the improvement of the quality of life of patients with equivalent rates of disease-free survival compared to radical mastectomies.Conclusion. Numerous studies have shown that breast-conserving surgery following neoadjuvant chemotherapy is the safe surgery with good oncologic outcomes and an alternative to radical mastectomies in breast cancer patients. However, further studies are required to determine the optimal safe resection margin width in patients with complete and partial responses to neoadjuvant chemotherapy.